Racial Differences in Mechanical Thrombectomy Utilization for Ischemic Stroke in the United States - Esenwa, Charles (Ethn Dis, 2020)
BACKGROUND: Compared with non-Hispanic Whites (NHW), racial-ethnic minorities bear a disproportionate burden of stroke and receive fewer evidence-based stroke care processes and treatments. Since 2015, mechanical thrombectomy (MT) has become standard of care for acute ischemic stroke (AIS) patients with proximal anterior circulation large vessel occlusion (LVO). OBJECTIVES: Our objectives were to: assess recent trends in nationwide MT utilization among patients with AIS; determine if there were racial differences; and identify what factors were associated with such differences. METHODS: We performed a retrospective cohort study using nationally representative data of a non-institutionalized population sample from 2006 to 2014 obtained from the Nationwide Inpatient Sample (NIS). We identified a total of 889,309 observations of AIS, of which there were 5,256 MT observations. RESULTS: In the fully adjusted model, rate of thrombectomy utilization was significantly lower in African Americans (AA) (OR .67, CI .58-.76, P<.001) compared with NHW and Hispanics (OR .94, CI .78-1.13, P=.5). CONCLUSION: We found a significant disparity in MT utilization for AA compared with NHW and Hispanics. More work is needed to understand the drivers of this racial disparity in stroke treatment.